RELATIONSHIP BETWEEN KPS AND BMT AT THE MODERN ISLAMIC BOARDING SCHOOL AL-RIFA'IE 2 MALANG - Fitriyah Mahdali; Ahmad Fauzi (Jurnal Penelitian Ilmiah INTAJ, 2022)
This study is a comparative analysis between savings and loan cooperatives and Islamic financial services cooperatives Baitul Maal wat Tamwil or BMT. This analysis was conducted to determine the relationship between cooperatives and BMT, so that they could provide real answers to the community, especially the public, that cooperatives and BMT are different entities. BMT is a microfinance institution that deals with middle- and lower-class entrepreneurs to help start up their business activities. BMT is intended to help the middle- and lower-class economies so that they can set up businesses without being caught up in loan sharks. Today, people often regard conventional cooperatives and BMT as financial institutions that are closely related to banks and interest. So they experience a deep dilemma when the need for business capital is not directly proportional to their mindset, they are in a dilemma if they have to pay interest and deal with moneylenders. This study is a field study (field research) with a qualitative approach conducted at Modern Islamic Boardng School al-Rifa'ie 2 Gondanglegi Malang Regency. Al-Rifa'ie has syari'ah cooperatives and BMTs that have won the trust of some people as financial service institutions that comply with Islamic law. The findings in the discussion resulted that cooperative and BMT in this case at Modern Islamic Boarding School al-Rifa'ie 2 have relations and differences. The relationship between the two lies in the legality of the institution, where BMT is under the auspices of the cooperative under its legal protection. The differences between the two are described in the comparative analysis table contained in the discussion chapter. This finding is expected to be able to provide a theoretical contribution to answer the community's doubts between conventional cooperatives and BMT.